Exophiala Dermatitidis Isolated From Blood In Patient With Steroid Use. (28th October 2020) - Yurtsever, N; Dougherty, P; Condon, S; Orsini, R; Berman, M; Berry, G J; Duong, S
Abstract: Casestudy: Exophiala dermatitidis is a dematiaceous mold that is associated with subcutaneous, central nervous system and pulmonary infections; osteomyelitis; and disseminated disease. Isolation of E. dermatitidis from patients with mild symptoms may be difficult to interpret whether is a contaminant or asymptomatic patient with serious infection. However, it is important to diagnose asymptomatic patients early in the stage because of up to 25% mortality rate. Results: 77-year-old male with history of chronic obstructive pulmonary disease presented to his pulmonologist with cough. He was started on azithromycin and steroids. His cough worsened and he was transitioned to levofloxacin with continuation of steroid treatment. In addition, he developed fatigue, weakness, poor appetite, chills and nights sweat along with some urinary complaints. His chest X-ray showed infiltrates and he was diagnosed with left lower lung pneumonia and urinary tract infection and was treated with doxycycline and ciprofloxacin. Blood cultures were drawn. Additional past medical history was not significant. Blood culture became positive on day 4 of incubation. Gram stain showed yeast-like cells, but the blood culture multiplex PCR was negative. Serum cryptococcus antigen was negative. Three days later, a dark shiny olive-colored colony with dark obverse side was isolated. It grew at 42 C. Microscopic examination revealed hyaline and pigmented hyphae with brown conidia. It was identified as Exophiala dermatitidis and confirmed by the state public health laboratory. Blood cultures drawn after hospital admission remained negative. Patient's symptoms improved with antibiotic treatment. Therefore the clinicians believed that the E. dermatitidis was a probable contaminant and patient was discharged with follow-up. During the follow-up process he developed respiratory infection with Coronavirus (HKU1, NL63, 229E, OC43). Follow-up continues. Conclusion: Blood cultures are not sensitive for mold infection especially for an uncommon contaminant like E. dermatitidis, it may be difficult to decide whether a positive culture is a real result or not. Fungal antigen tests such as beta-D-glucan test may be helpful in distinguishing between invasive infection and contaminant. Additionally, we believe that in our case, steroid use could have caused a temporary immunosuppression and led to Exophiala dermatitidis infection.